Alexandr Yevgenyevich Loskutov - DMA, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 60th birthday of the Head of the Department of Traumatology and Orthopaedics of Dniepropetrovsk State Medical Academy, Vice-President of the Ukrainian Association of Orthopaedic Traumatologists, Honoured Worker of Science and Engineering of Ukraine, winner of the State Prize of Ukraine, Doctor of Medical Science, Prof. Loskutov Alexandr Yevgenyevich.